First Assessment of Plasticizers in Marine Coastal Litter-Feeder Fauna in the Mediterranean Sea - Sabrina Lo Brutto; Davide Iaciofano; Vincenzo Lo Turco; Angela Giorgia Potortì; Rossana Rando; Vincenzo Arizza; Vita Di Stefano (Toxics, 2021)
Micro and nanoplastics are harmful to marine life due to their high level of fragmentation and resistance to degradation. Over the past two decades, marine coastal sediment has shown an increasing amount of microplastics being a sort of trap for debris wastes or chemicals. In such an environment some species may be successful candidates to be used as monitors of environmental and health hazards and can be considered a mirror of threats of natural habitats. Such species play a key role in the food web of littoral systems since they are litter-feeders, and are prey for fishes or higher trophic level species. A preliminary investigation was conducted on five species of small-sized amphipod crustaceans, with the aim to understand if such an animal group may reflect the risk to ecosystems health in the central Mediterranean area, recently investigated for seawater and fish contamination. This study intended to gather data related to the accumulation of plasticizers in such coast dwelling fauna. In order to detect the possible presence of xenobiotics in amphipods, six analytes were scored (phthalic acid esters and non-phthalate plasticizers), identified and quantified by the gas chromatography mass spectrometry (GC-MS) method. The results showed that among all the monitored contaminants, DEP and DiBP represented the most abundant compounds in the selected amphipods. The amphipod crustaceans analyzed were a good tool to detect and monitor plasticizers, and further studies of these invertebrates will help in developing a more comprehensive knowledge of chemicals spreading over a geographical area. The results are herein presented as a starting point to develop baseline data of plasticizer pollution in the Mediterranean Sea.